Community supervision officers' perspective on body worn cameras - Edwards, Mari-Esther (Kansas State University, 2022)
The purpose of this dissertation is to examine how community supervision officers (CSO) and administrators perceive the use of body-worn cameras (BWCs) by a community supervision agency. Community supervision agencies provide supervision to criminal offenders in lieu of them being incarcerated in a prison or jail. The two main types of community supervision are probation and parole. A CSO’s role involves using both punitive (control) and rehabilitative resources (referring clients to treatment programs) in the provision of case management services (Healey, 1999). This was a qualitative exploratory study. Seventeen (17) semi-structured interviews were conducted over Zoom with a community supervision department in the southern region of the United States to answer the two overarching research questions: (1) How do CSOs and administrators view the potential impacts of BWCs on behavior, intra-departmental relations, and public relations? and (2) How do CSOs and administrators perceive the use of BWCs will shape the execution of their day-to-day work duties? Based on the results of this dissertation, respondents indicated that BWCs may facilitate the fulfillment of various case management duties, officer training, and client and officer accountability; however, they were concerned that these devices may hinder rapport between the client and CSO, create privacy issues, present technological problems, and incur a financial burden. Agencies may want to reconsider implementing BWCs until greater clarity is gained regarding the impact of such devices on the department’s legitimacy within the community, accountability among officers, and prevalence of citizen complaints. Further, it is recommended that a cost benefit analysis be conducted prior to implementing BWCs within community supervision agencies.
Keywords: Body-worn cameras; Community supervision; Probation officers; Parole officers